Performance of fall and winter crops in a no tillage system in west Paraná State - Albrecht, Leandro Paiola; Krenchinski, Fábio Henrique; Gomes, Alcides de Oliveira; Albrecht, Alfredo Junior Paiola; Mattiuzzi, Mateus Dalpubel; Cassol, Marcelo (Acta Scientiarum. Agronomy, 2018)
The long-term exploitation of natural resources by agricultural activities has resulted in the need for alternative measures to restore degraded soil. The cultivation of cover crops can generate great benefits for agricultural systems, enabling the exploitation of natural resources, including water, light and nutrients, as well as the recovery of degraded soils. This work aimed to assess the coverage rate, fresh mass and dry mass of cover crops from fall and winter as well as the floristic composition of the weeds. The work was conducted in field conditions in soil classified as eutroferric Red Oxisol in the region of the city of Palotina, Paraná State, Brazil, using a random block experimental design with four replications. The treatments consisted of seven cover cultures: wild radish, linseed, triticale, rye, rapeseed, crambe, oats and fallow. The species with the highest coverage rates and fresh mass and dry mass values were wild radish, rapeseed and crambe. In the floristic and phytosociological data, the species with the highest incidence were Amaranthus retroflexus, Commelina benghalensis L., Brachiaria plantaginea and Gnaphalium spicatum.